Influence of Ir and La substitution on the thermal transport properties of YbRh2Si2. Issue 3 (22nd January 2013) - Stockert, Ulrike; Pfau, Heike; Hartmann, Stefanie; Lausberg, Stefan; Friedemann, Sven; Krellner, Cornelius; Wirth, Steffen; Geibel, Christoph; Steglich, Frank
Abstract We investigate the influence of small amounts of Ir and La substitution on the low‐temperature thermal conductivity κ and thermopower S of YbRh2Si2. While the thermal conductivity is reduced in both cases due to the introduction of additional impurities, the effect on the thermopower is non‐uniform: Ir substitution leads to a reduction of the absolute value of the thermopower. This is attributed largely to an enhanced disorder scattering. On the other hand, La substitution increases the absolute thermopower values. We discuss the possibility that this is due to band structure modifications upon doping into the Yb sublattice.